Development of stream classification system on river catchment management with environmental statistical techniques approval - Mohd Khairul Amri, Kamarudin; Hafizan, Juahir; Mohd Ekhwan, Toriman; Roslan, Umar; Azizah, Endut (2016)
Stream classification system is very important to identify the characteristic of stream on the basin. Stream behaviors can provide guidance for future problem in this basin. This study discusses on the development of stream classification system on tropical areas with statistical approval based on Remote Sensing (RS), Geographical Information System (GIS), and river survey database based on Rosgen Classification System. The environmental statistical techniques have been used to identify the clustering development on the tropical stream system using Hierarchical Agglomerative Cluster Analysis (HACA), Discriminant Analysis (DA) and Principal Component Analysis (PCA). The HACA results indicated the main of tropical stream system has been classed into three main clusters as upstream reach, middle stream reach and downstream reach at the river basin. Based on calibration and validation model with DA shows 100% convinced. The PCA indicates that there are three variables that have significant correlations with is domination slope R2 0.796, Bank full width-to-depth ratio with R2 -0868, and sinuosity with R2 0.557. Model of stream classification system with future geomorphology process and problem expectations is produced where the first class considered in terrace and valley erosion zone, second class in a low terrace of land near the channels and sediment transports zone, and third class in valley deposition and floodplain zone. From this result, this study can produce the basic information or database to understand the characteristics of the stream classification system behavior on tropical areas. This result is also very important to local authorities to make decisions according to the cluster or guidelines for future study.